Surface production operations. Volume 2, Design of gas-handling systems and facilities - Arnold, Ken, 1942-; Stewart, Maurice (Houston, Tex. : Gulf Pub. Co., 1998)
This revised edition puts the most current information about gas-handling systems and facilities at your fingertips. The authors channeled their classroom and field experience into this volume, which features many new sections such as: * Heat recovery units * Kinetic inhibitors and anti-agglomerators * Trays and packing for distillation and absorption towers * Compressor valves * Foundation design considerations for reciprocating compressors * Pressure vessel issues and components * Nox reduction in engines and turbines * Safety management systems This book walks you through the equipment and processes used in gas-handling operations to help you design and manage a production facility. Production engineers will keep this volume on the desktop for the latest information on how to DESIGN, SPECIFY, and OPERATE gas-handling systems and facilities. The book allows engineers with little or background in production facility design to easily locate details about equipment, processes, and design parameters. With this volume, you will more completely comprehend the techniques of handling produced fluids from gas wells so your facility can be more efficient and productive. * Revised edition puts the most current information about gas-handling systems at your fingertips * Features brand new sections!
Overview of gas-handling facilities -- Heat transfer theory -- Heat exchangers -- Hydrates -- LTX units and indirect fired heaters -- Condensate stabilization -- Acid gas treating -- Gas dehydration -- Gas processing -- Compressors -- Reciprocating compressors -- Mechanical design of pressure vessels -- Pressure relief -- Safety systems -- Valves, fittings, and piping details -- Prime movers -- Electrical systems.
Includes bibliographical references and indexes.
Keywords: Petroleum engineering -- Equipment and supplies; Oil fields -- Equipment and supplies; Oil fields -- Production methods; Electronic books